2021
DOI: 10.1111/jocd.14023
|View full text |Cite
|
Sign up to set email alerts
|

Histological and immunohistochemical changes in facial skin treated with combined ablative and non‐ablative laser therapy

Abstract: The appearance of one's skin reflects a person's general health and is one of the main indicators of human age. 1 As skin ages, it tends to become uneven in color, roughened, lax, and wrinkled due to intrinsic and extrinsic factors (eg, photodamage). A major feature of aged skin is fragmentation of the dermal collagen matrix. Fragmentation results from the actions of specific enzymes (matrix metalloproteinases) and impairs the structural integrity of the dermis. Fibroblasts that produce and organize the collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…The study found that hybrid fractional laser treatment can be used safely and effectively to treat photodamaged skin with high patient satisfaction and minimal adverse events. In another study, Shanina et al 11 focused on facial skin rejuvenation in 14 patients, using a dual-wavelength protocol combining a fractional ablative (2,940 nm) laser and a non-ablative (1,064 nm) laser. The results showed significant improvements in all areas of the face as compared to the pretreatment baseline, which was also confirmed by histology.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that hybrid fractional laser treatment can be used safely and effectively to treat photodamaged skin with high patient satisfaction and minimal adverse events. In another study, Shanina et al 11 focused on facial skin rejuvenation in 14 patients, using a dual-wavelength protocol combining a fractional ablative (2,940 nm) laser and a non-ablative (1,064 nm) laser. The results showed significant improvements in all areas of the face as compared to the pretreatment baseline, which was also confirmed by histology.…”
Section: Discussionmentioning
confidence: 99%
“…The heat pulses penetrate the skin to approximately 0.5 mm in depth, resulting in paracrine signaling that activates fibroblasts to initiate regenerative processes in the skin. 23 , 24 …”
Section: Introductionmentioning
confidence: 99%
“…The heat pulses penetrate the skin to approximately 0.5 mm in depth, resulting in paracrine signaling that activates fibroblasts to initiate regenerative processes in the skin. 23,24 The aim of this retrospective clinical study was to assess the effectiveness of the novel non-ablative Er:YAG laser treatment, either as a monotherapy or in combination with subcutaneous injections of PRP to the scalp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SMOOTH™ mode denotes trains of short subablative pulses of laser light, which is absorbed in the most superficial (<10 µm) layer of the skin, leaving only heat to diffuse to deeper layers (400 µm). This treatment modality results in paracrine signaling that activates fibroblasts and initiates regenerative processes in the skin 14,15 and has already been used for stimulation of hair growth. 16…”
Section: Introductionmentioning
confidence: 99%